Skull Base Meningiomas and Cranial Nerves Contrast Using Sodium Fluorescein: A New Application of an Old Tool - da Silva, Carlos Eduardo; da Silva, Vinicius Duval; da Silva, Jefferson Luis Braga (Journal of Neurological Surgery Part B: Skull Base, 2014)
Objective The identification of cranial nerves is one of the most challenging goals in the dissection of skull base meningiomas. The authors present an application of sodium fluorescein (SF) in skull base meningiomas with the purpose of improving the identification of cranial nerves.Design A prospective study within-subjects design.Setting Hospital Ernesto Dornelles, Porto Alegre, Brazil.Participants Patients with skull base meningiomas.Main Outcomes Measures Cranial nerve identification.Results The group of nine meningiomas was composed of one cavernous sinus, three petroclival, one tuberculum sellae, two sphenoid wing, one olfactory groove, and one temporal floor meningioma. The SF enhancement in all tumors was strong, and the contrast with cranial nerves clearly evident. There were one definite olfactory nerve deficit, one transient abducens deficit, and one definite hemiparesis. All lesions were resected (Simpson grades 1 and 2). The analysis of the difference of the delta SF wavelength between the meningiomas and cranial nerve contrast was performed by the Wilcoxon signed rank test and showed p = 0.011.Conclusions The contrast between the enhanced meningiomas and cranial nerves was evident and assisted in the visualization and microsurgical dissection of these structures. The anatomical preservation of these structures was improved using the contrast.
Keywords: cranial nerves; fluorescent markers; fluorescent-guided surgery; meningiomas; sodium fluorescein